INTEGRATION OF ISLAMIC PHILANTHROPY WITH FINANCIAL TECHNOLOGY: The Case Study of Waqf towards Sustainable Funding in Indonesia - Ulum, Kefi Miftachul; Ariyanti, Sari; Witro, Doli; Nasyiah, Iffaty (Jurisdictie: Jurnal Hukum dan Syariah, 2025)
The rapid expansion of Indonesia’s digital economy, bolstered by evolving financial regulations, presents a strategic opportunity to integrate Islamic philanthropy—particularly waqf—into fintech-based funding systems. This study explores the potential integration of waqf instruments within securities crowdfunding, as governed by OJK Regulation No. 57 of 2020 and its amendment, OJK Regulation No. 16 of 2021. The growth in sukuk issuances—from 59 in August 2023 to 105 by May 2024, comprising 30% of all securities—demonstrates a promising avenue for channeling waqf funds to support MSMEs and drive socio-economic development. Employing a normative legal research methodology, this study utilizes statutory and conceptual analysis, drawing on primary legal sources related to waqf and crowdfunding, as well as secondary data from the Financial Services Authority (OJK) and the Central Securities Depository (KSEI). Through descriptive-analytical methods and integrative legal theory, the research examines how regulatory frameworks can be aligned. The findings indicate a strong legal synergy between Islamic waqf law and fintech regulations, facilitating the development of a productive, Sharia-compliant waqf investment model. This study offers a conceptual and regulatory roadmap for leveraging waqf funds through digital platforms, enhancing their sustainability, accountability, and role in promoting inclusive Islamic economic growth. Ekspansi pesat ekonomi digital Indonesia yang didukung oleh regulasi keuangan yang terus berkembang menghadirkan peluang strategis untuk mengintegrasikan filantropi Islam—khususnya wakaf—ke dalam sistem pendanaan berbasis fintech. Studi ini mengeksplorasi potensi integrasi instrumen wakaf dalam skema securities crowdfunding sebagaimana diatur dalam Peraturan OJK Nomor 57 Tahun 2020 dan perubahannya, yakni Peraturan OJK Nomor 16 Tahun 2021. Peningkatan jumlah penerbitan sukuk—dari 59 pada Agustus 2023 menjadi 105 pada Mei 2024, yang mencakup 30% dari seluruh surat berharga—menunjukkan jalur yang menjanjikan untuk menyalurkan dana wakaf guna mendukung UMKM dan mendorong pembangunan sosial ekonomi. Dengan menggunakan metode penelitian hukum normatif, studi ini menerapkan pendekatan analisis yuridis dan konseptual, dengan merujuk pada sumber hukum primer terkait wakaf dan crowdfunding, serta data sekunder dari Otoritas Jasa Keuangan (OJK) dan Kustodian Sentral Efek Indonesia (KSEI). Melalui metode deskriptif-analitis dan pendekatan teori hukum integratif, penelitian ini mengkaji bagaimana kerangka regulasi dapat diselaraskan. Temuan menunjukkan adanya sinergi hukum yang kuat antara hukum wakaf Islam dan regulasi fintech, yang memungkinkan pengembangan model investasi wakaf yang produktif dan sesuai dengan prinsip syariah. Studi ini menawarkan peta jalan konseptual dan regulatif untuk memanfaatkan dana wakaf melalui platform digital, guna meningkatkan keberlanjutan, akuntabilitas, serta peranannya dalam mendorong pertumbuhan ekonomi Islam yang inklusif.